2017
DOI: 10.1111/1462-2920.13808
|View full text |Cite
|
Sign up to set email alerts
|

VapC toxins drive cellular dormancy under uranium stress for the extreme thermoacidophile Metallosphaera prunae

Abstract: Summary When abruptly exposed to toxic levels of hexavalent uranium, the extremely thermoacidophilic archaeon Metallosphaera prunae, originally isolated from an abandoned uranium mine, ceased to grow, and concomitantly exhibited heightened levels of cytosolic ribonuclease activity that corresponded to substantial degradation of cellular RNA. The M. prunae transcriptome during ‘uranium-shock’ implicated VapC toxins as possible causative agents of the observed RNA degradation. Identifiable VapC toxins and PIN-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
0
15
1
Order By: Relevance
“…3). Previous work showed that sudden additions of uranium to cultures triggered a dormant phase in M. prunae (but not in M. sedula) (20) involving VapC toxin-antitoxin loci (17,20); a similar phenomenon could be a factor here. These results indicate that chemolithoautotrophic metabolism could be supported by Fe(II) oxidation in these Metallosphaera species and that the use of V and Mo as electron mediators to recycle Fe(III) to Fe(II) through their oxidation bolstered respiratory processes.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…3). Previous work showed that sudden additions of uranium to cultures triggered a dormant phase in M. prunae (but not in M. sedula) (20) involving VapC toxin-antitoxin loci (17,20); a similar phenomenon could be a factor here. These results indicate that chemolithoautotrophic metabolism could be supported by Fe(II) oxidation in these Metallosphaera species and that the use of V and Mo as electron mediators to recycle Fe(III) to Fe(II) through their oxidation bolstered respiratory processes.…”
Section: Resultsmentioning
confidence: 63%
“…Oxygen consumption assays showed a direct reduction in the rate of oxygen consumption for iron-limited conditions, which was recovered by the addition of ferric chloride. However, the recovery was not complete for M. prunae and could indicate a VapC toxin-mediated dormant phase, previously observed during uranium "shock" for M. prunae (17,20). Solubilized molybdenum and vanadium anions could exist in more than one oxidation state, with a higher oxidation state possible, and thus serve as energetic substrates capable of being biooxidized.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…S5). The VapC4 toxin is a well-known ribonuclease belonging to the VapC group of the PIN superfamily (22), indicating that the nuclease domain of Aq880 is responsible for cleavage catalysis.…”
Section: Cryo-em Single-particle Analysis Of Aq880mentioning
confidence: 99%